Hit Triage Using Efficiency Indices after Screening of Compound Libraries in Drug Discovery - Reitz, Allen B.; Smith, Garry R.; Tounge, Brett A.; Reynolds, Charles H. (Current Topics in Medicinal Chemistry, 2009)
Fragment-based drug discovery (FBDD) is an important new tool to understand the molecule basis of ligandbiological target interactions. By combining optimal fragments, it is often possible to construct larger molecular weight compounds that have greater potency in a shorter period of time than can been achieved by the initial screening of larger molecular weight compound libraries. Alternatively, if screening of more traditional larger libraries has occurred, then it may be possible to analyze the data during the process of hit triage in such as way as to essentially adopt a fragment-based approach in reverse. In this review, we highlight general principles associated with the efficiency indices such as Ligand Efficiency (LE) in which screening data is normalized for biophysical properties such as molecular size. We further focus on the concept of Fit Quality (FQ), which standardizes LE values across molecular weight for more realistic, direct comparison. Using these simple concepts, one can apply FBDD routinely in the stage of hit triage when evaluating the data obtained after screening of compound libraries in drug discovery.